Effect of Workload, Work Stress, Technical Skills, Self-Efficacy, and Social Competence on Medical Personnel Performance - Tasya Kamila Andiani; Oscar Jayanagara (Pandawan, 2023)
This research focuses on analyzing the influence of Workload, stress, technical skills, self-efficacy, and social competence on the performance of medical personnel in the era of the Covid-19 pandemic. This research includes quantitative descriptive analysis with a cross-sectional approach. The dependent variables in this study are the performance of medical personnel, while the independent variables are Workload, work stress, technical skills, self-efficacy, and social competence. Sample an in this study is a part of the medical personnel who provide services to a Covid-19 patient ataSukajadi Regional General Hospital, Banyuasin, South Sumatra, which totals 130 people. Take a sample using purposive sampling. Data analysis and processing using the Multiple Linear Regression method. The results showed that Workload had a negative and significant effect on the Performance of Medical Personnel at the Sukajadi Regional General Hospital, Banyuasin, South Sumatra (sig value (0.022) <Level of Significant (0.05)), Work Stress had a negative, but not significant effect on the Performance of Medical Personnel at the Sukajadi Regional General Hospital, Banyuasin, South Sumatra (sig value (0.262) > Level of Significant (0.05)), technical Skills have a positive and significant effect on the Performance of Medical Personnel at the Sukajadi Regional General Hospital, Banyuasin, South Sumatra (sig value (0.046) <Level of Significant (0.05)), Self Efficacy has a positive and significant influence on the Performance of Medical Personnel at the Sukajadi Regional General Hospital, Banyuasin, South Sumatra (sig value (0.040) <Level of Significant (0.05 )), Social Competence has a positive and significant influence on the Performance of Medical Personnel at the Sukajadi Regional General Hospital, Banyuasin, South Sumatra (sig value (0.000) <Level of Significant (0.05)), and Workload, Work Stress, Technical Skills, Self Efficacy, and Social Competence have a joint influence on the Performance of Medical Personnel at the Sukajadi Regional General Hospital, Banyuasin, South Sumatra (sig value (0.000) <Level of Significant (0.05)). If Workload, Work Stress, Technical Skills, Self Efficacy, and Social Competence increase together, then the Performance of Medical Personnel at the Sukajadi Regional General Hospital, Banyuasin, South Sumatra, has increased significantly